PENGARUH VARIASI KUAT ARUS LAS LISTRIK PADA PENGELASAN BAJA C45 DENGAN SUDUT KAMPU V GANDA TERHADAP UJI TARIK DAN UJI IMPAK - Taufik Sutoyo (Universitas Harapan Medan, 2019)
The research of Carbide Cut Chisel concludes that every time there is a change in the execution of the work, indirectly changes in cutting speed, heat energy in metal cutting, heat due to chip chisel friction, heat arising from the scissors force. although done with a fixed force from this result data is obtained for processing time 2, 4 and 8 hours cutting speed (Vc) = 2.66 m / s, 3.16 m / s, 3.83 m / s with cutting power ( Pc) = 14.77 Hp and Electro Motor Power (Pg) = 18.7 Hp. For forces that occur in the turning process obtained Fc = 350 kg, Ft = 180.3 kg, Fs = 280.9 kg, Fns = 350 kg, Fv = 397 kg, Ff = 218 kg, Fn = 332 kg. The results obtained for Pm are 102 kal / s, 169kal / s for Pf is 2172 kal / s, 2580 kal / s, 3127 kal / s for Ps is 128 kal / s, 152 kal / s 184 cal / s. Temperature Zone 1 and Temperature Zone 2 are for Өm are 76.940C, 76.93 0C, 73.28 0C and Өf are 4.82 0 C with a time of 2.4 and 8 hours. Next for mtm = 584 0C, 583 0 C, 582 0C. For ∆ts are: 8.6 0C, 8.5 0C, 8.4 0C. For ∆to = Room temperature is taken 28 0C. For Maximun Temperature ∆. max = 620.6 0C, 619.50C, 618.4 0C.